1972
DOI: 10.1037/h0032339
|View full text |Cite
|
Sign up to set email alerts
|

Changes in EEG alpha frequency and evoked response latency during solitary confinement.

Abstract: One week of solitary confinement of prison inmates produced significant changes in their EEG frequency and visual evoked potentials (VEP) that parallel those reported in laboratory studies of sensory deprivation. EEG frequency declined in a nonlinear manner over the period. VEP latency, which decreased with continued solitary confinement, was shorter for these 5s than for control 5s whose VEP latency did not change over the same period. Experimental 5s who had been in prison longer had shorter VEP latencies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 14 publications
(17 reference statements)
1
24
0
Order By: Relevance
“…Reduced alpha power and elevated theta power suggest a deficit in cortical maturation in CAUG group. This pattern of immature neuronal activity, characterized by greater power in the slower frequency band combined with reduced power in a faster frequency, has been observed in children reared in social isolation and deprivation (Gendreau, Freedman, Wilde, & Scott, ; Zubek, Welch, & Saunders, ), extreme stress (Montes, Alcántara, Cedeño, García, & Rojas, ), poor environmental stimulation (Otero, , ) and adverse family environment (Bick, Palmwood, Zajac, Simons, & Dozier, ). Bick et al () examined the relations between early family adversity and brain electrical activity and found that early family adversity was associated with greater power in theta frequency band and lower power in alpha frequency band in middle childhood.…”
Section: Discussionmentioning
confidence: 74%
“…Reduced alpha power and elevated theta power suggest a deficit in cortical maturation in CAUG group. This pattern of immature neuronal activity, characterized by greater power in the slower frequency band combined with reduced power in a faster frequency, has been observed in children reared in social isolation and deprivation (Gendreau, Freedman, Wilde, & Scott, ; Zubek, Welch, & Saunders, ), extreme stress (Montes, Alcántara, Cedeño, García, & Rojas, ), poor environmental stimulation (Otero, , ) and adverse family environment (Bick, Palmwood, Zajac, Simons, & Dozier, ). Bick et al () examined the relations between early family adversity and brain electrical activity and found that early family adversity was associated with greater power in theta frequency band and lower power in alpha frequency band in middle childhood.…”
Section: Discussionmentioning
confidence: 74%
“…The distribution of greater power in slower frequencies of the EEG is not only characteristic of extreme deprivation or social isolation ( Gendreau et al, 1972 , Marshall and Fox, 2004 , Zubek et al, 1963 ), but has been observed in typically developing populations of children living in impoverished environments. A number of studies have shown that children living in low resource homes (e.g., poor nutrition, unsanitary living conditions, less responsive or sensitive caregiving) show a similar “immature” pattern of EEG activity as we have observed in the BEIP sample.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies by Gendreau and colleagues (Ecclestone et al, 1974;Gendreau & Bonta, 1984;Gendreau et al, 1968Gendreau et al, , 1970Gendreau et al, , 1972 used repeated measures experimental designs over periods of up to 10 days to explore the effects of segregation on psychological and physiological measures. Few negative impacts of segregation were found over these brief time periods.…”
Section: Longitudinal Designsmentioning
confidence: 99%
“…Several of these studies have been experimental in nature in that inmates who volunteer to be randomly assigned to either segregation or comparison conditions for a short period of time (e.g., Ecclestone, Gendreau, & Knox, 1974;Gendreau & Bonta, 1984;Gendreau, Freedman, Wilde, & Scott, 1968, 1972Gendreau, McLean, Parsons, Drake, & Ecclestone, 1970). These studies tend to show little impact of segregation on mental well-being but can be criticized for lacking ecological validity by using participants who volunteered to be placed in segregation, using small samples sizes, and for being short-term, all of which do not match the current reality of how AS exists in U.S. prisons today.…”
Section: Quantitative Researchmentioning
confidence: 99%